Jejunal diverticulitis - Ray, M. S.; Deepak, B. S. (International Surgery Journal, 2016)
Jejunal diverticulosis is a rare condition associated with small bowel obstruction, bleeding, or perforation. It diverticulitis should be considered as an important differential in elderly patients who present with acute abdominal pain. We have brought forward a rare case report of multiple jejunal diverticula and peritonitis due to perforated diverticulum, making the management challenging and interesting.